National Cancer Institute Workshop on Chemopreventive Properties of Nonsteroidal Anti-Inflammatory Drugs: Role of COX-Dependent and -Independent Mechanisms - Daniel H. Hwang; Victor Fung; Andrew J. Dannenberg (Neoplasia: An International Journal for Oncology Research, 2002)
A workshop, “Chemopreventive properties of nonsteroidal anti-inflammatory drugs (NSAIDs): Role of COXdependent and -independent mechanisms,” sponsored by the Chemical and Physical Carcinogenesis Branch, Division of Cancer Biology of the National Cancer Institute, was held in Rockville, Maryland, on January 8, 2001. The workshop was composed of two parts: oral presentations by a series of speakers, and a group discussion of preselected topics.